PERKEMBANGAN PENDIDIKAN ISLAM AWAL: DAR AL-ARQAM , KUTTAB DAN MASJID - Yanda Amalia; Faridi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the development of early Islamic education through three main institutions: Dar Al-Arqam, Kuttab, and the Mosque. These institutions played a crucial role in establishing the foundations of the Islamic educational system from the time of the Prophet Muhammad (peace be upon him) to the early period of Islamic civilization. This research is motivated by the importance of understanding the historical roots of Islamic education to ensure that its fundamental values remain relevant in contemporary educational contexts. The research employs a library research method by analyzing various academic sources, including books on the history of Islamic education, scientific journals, and relevant scholarly works. The findings indicate that Dar Al-Arqam functioned as the first center of Islamic education, focusing on strengthening faith and character development in a secret and secure environment amid Quraysh persecution. Kuttab emerged as a basic educational institution emphasizing literacy skills, Qur’anic learning, and moral education for Muslim children. Meanwhile, mosques developed as open educational centers that integrated religious, social, and intellectual activities. These three institutions illustrate the gradual evolution of Islamic education, highlighting a balanced integration of faith, knowledge, and moral practice. The educational values established during the early Islamic period have proven to be a solid foundation for the sustainability and development of Islamic education to the present day.